Decreased cardiovascular mortality in the ITALUNG lung cancer screening trial: Analysis of underlying factors. (December 2019) - Puliti, Donella; Mascalchi, Mario; Carozzi, Francesca Maria; Carrozzi, Laura; Falaschi, Fabio; Paci, Eugenio; Lopes Pegna, Andrea; Aquilini, Ferruccio; Barchielli, Alessandro; Bartolucci, Maurizio; Grazzini, Michela; Picozzi, Giulia; et al.
Highlights: LDCT screening for lung cancer is also capable to detect CACs. CV mortality significantly decreased among screened subjects. Subjects with screen-detected CAC experienced lower CV mortality than expected. The knowledge of presence/absence of CAC may have induced preventing actions. Abstract: Objectives: In the ITALUNG lung cancer screening trial after 9.3 years of follow-up we observed an unexpected significant decrease of cardiovascular (CV) mortality in subjects invited for low-dose CT (LDCT) screening as compared to controls undergoing usual care. Herein we extended the mortality follow-up and analyzed the potential factors underlying such a decrease. Materials and methods: The following factors were assessed in screenes and controls: burden of CV disease at baseline, changes in smoking habits, use of CV drugs and frequency of planned vascular procedures after randomisation. Moreover, in the screenes we evaluated inclusion of presence of coronary artery calcification (CAC) in the LDCT report form that was transmitted to the participant and his/her General Practitioner. Results: The 2-years extension of follow-up confirmed a significant decrease of CV mortality in the subjects of the active group compared to control subjects (15.6 vs 34.0 per 10, 000; p = 0.001) that was not observed in the drops-out of the active group. None of the explaining factors we considered significantly differed between active and control group. However, the subjects of the active group with reported CAC experienced a not significantly lower CV mortality and showed a significantly higher use of CV drugs and frequency of planned vascular procedures than the control group. Conclusions: LDCT screeni ng for lung cancer offers the opportunity for detection of CAC that is an important CV risk factor. Although the underlying mechanisms are not clear, our results suggest that the inclusion of information about CAC presence in the LDCT report may represent a candidate factor to explain the decreased CV mortality observed in screened subjects of the ITALUNG trial, possibly resulting in intervention for patient care to prevent CV deaths. Further studies investigating whether prospective reporting and rating of CAC have independent impact on such interventions and CV mortality are worthy.